2017
DOI: 10.25115/ejrep.41.16042
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship between Academic Procrastination, Satifaction with Academic Life and Academic Performance

Abstract: Introduction. Procrastination has become one of the most researched topics due its adverse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
(52 reference statements)
3
23
0
4
Order By: Relevance
“…The Clute Institute younger students procrastinated more often than female and older students. These findings are similar to the ones reported by Balkis and Duru (2017) who argued that male students were more vulnerable to the destructive effects of academic procrastination compared to female students. The reasons for these differences can not be established in this study and should be the subject of further research in this area.…”
Section: Copyright By Author(s); Cc-bysupporting
confidence: 90%
See 1 more Smart Citation
“…The Clute Institute younger students procrastinated more often than female and older students. These findings are similar to the ones reported by Balkis and Duru (2017) who argued that male students were more vulnerable to the destructive effects of academic procrastination compared to female students. The reasons for these differences can not be established in this study and should be the subject of further research in this area.…”
Section: Copyright By Author(s); Cc-bysupporting
confidence: 90%
“…Research in this area is limited. Balkis and Duru (2017) found that male students procrastinated more often than female students. Male students also suffered more negative consequences related to procrastination compared to female students such as lower grades and lower satisfaction with the college experience.…”
Section: Procrastination and College Studentsmentioning
confidence: 92%
“… Non-Regulation of Health behavior (NRH) refers to lack of proactivity and the absence of personal health-regulating behaviors. This is the conceptual equivalent of reactivity [ 19 , 25 , 33 ]. In this case, the student is fully dependent on whatever external regulation is provided by the context.…”
Section: Introductionmentioning
confidence: 99%
“…In male students, for example, it predicts psychological individualization, self-control, and academic performance. But in the case of girls, the exclusion of emotional conflict with the parents rather than individualization was a predictor of self-control and academic procrastination, and for example, in the individual study, no difference in terms of gender was reported in the rate of procrastination [17,18]. In Milgram NA, et al, study, anxiety was weakly associated with delay itself; it meant that anxiety was not the main reason of procrastination.…”
Section: Resultsmentioning
confidence: 86%